Conversion: non-réciproque – réciproque. Variantes syntaxiques - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2010)
The present paper is devoted to the concept of reciprocity and to reciprocal expressions, which are divided into two main classes. Those belonging to the first of them signify reciprocity on their own, i.e. without any additional reciprocal markers. The other class contains expressions that acquire ability to refer to reciprocal states of affairs only as a result of appropriate transformations. Different reciprocal markers – grammatical, lexical and quantifying – are singled out and thoroughly characterized. Their use results in converting non-reciprocal signs into reciprocal ones. They are applied according to the part of speech of a modified term. The conclusion to be drawn from this analysis revolves around the discrepancy between morphological and syntactic means of reciprocal transformation. While the former ones are rather scanty, the latter are largely used in contemporary French.